Modelling of high temperature furnaces under air-fuel and oxygen enriched conditions. (25th May 2018) - Mayr, B.; Prieler, R.; Demuth, M.; Hochenauer, C.
Highlights: CFD modelling of air-fuel and oxy-fuel combustion in industrial processes. Development of a 0/1D model to predict the temperature and heat transfer. Comparison of the simplified model with experimental data and CFD. Investigation of a lab-scale, melting and a walking hearth reheating furnace. Abstract: A zero/one dimensional thermodynamic model was developed that can be used to determine the influence of oxygen enriched combustion (OEC) on the heat transfer, gas, and wall temperatures in a furnace. The model uses simple thermodynamic correlations, which makes it very time efficient (with calculation times of a few seconds), and therefore mean that it can be used in Microsoft Excel. This model was used to calculate the heat flux to a thermal load and the main temperatures (gas and wall) in a lab-scale furnace and industrial scale furnaces. The results were compared with both experimental measurements and the results of CFD calculations. The thermodynamic model showed good agreement with the measurements and the results of the CFD calculations, considering its simplicity. Thus, this model shows high potential for use to quickly determine the effects of OEC on industrial furnaces.